A new system for analyzing swim fin propulsion based on human kinematic data - Nicolas, G.; Bideau, B.; Bideau, N.; Colobert, B.; Le Guerroue, G.; Delamarche, P. (Journal of Biomechanics, 2010)
The use of swim fins has become popular in various water sport activities. While numerous models of swim fin with various innovative shapes have been subjectively designed, the exact influence of the fin characteristics on swimming performance is still much debated, and remains difficult to quantify. To date, the most common approach for evaluating swim fin propulsion is based on the study of "swimmer-fins" as a global system, where physiological and/or biomechanical responses are considered. However, reproducible swimming technique is difficult (or even impossible) to obtain on human body and may lead to discrepancies in data acquired between trials. In this study, we present and validate a new automat called HERMES which enables an evaluation of various swim fins during an adjustable, standardized and reproducible motion. This test bench reliably and accurately reproduces human fin-swimming motions, and gives resulting dynamic measurements at the ankle joint. Seven fins with various geometrical and mechanical characteristics were tested. For each swim fin, ankle force and hydromechanical efficiency (useful mechanical power output divided by mechanical power input delivered by the motors) were calculated. Efficiencies reported in our study were high (close to 70% for some swim fins) over a narrow range of Strouhal number (St) and peaks within the interval 0.2<St<0.4, as shown in previous studies on flying or swimming animals. Therefore, an interesting prospect in this work would be to accurately study the impact of adjustable fin kinematics and material (design and mechanical properties) on the wake structure and on efficiency.